Are companies less environmentally-friendly due to the crisis?: Evidence from Europe - Miras-Rodríguez,María del Mar (2015)
Academicians and managers are worried about what is going to happen with the Environmental Responsibilities of companies due to the worsening of their financial situation caused by the severe economic crisis that is significantly affecting them. The aim of this paper is to study the effect of the crisis on the environmental behavior of companies from the European countries that are suffering the financial crisis most (Greece, Ireland, Italy, Portugal, and Spain) through a data panel study between 2005 and 2012. The results show surprisingly that proactive, environmentally-friendly actions have not decreased during the crisis but rather that the crisis has meant an increase in environmental commitment. This is strongly motivated by the Product Innovation actions which attain the highest increase.